2015
DOI: 10.1155/2015/592953
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogens Associated with Acute Diarrhea in Children from Households with High Socioeconomic Level in Uruguay

Abstract: Infectious diarrhea, a common disease of children, deserves permanent monitoring in all social groups. To know the etiology and clinical manifestations of acute diarrhea in children up to 5 years of age from high socioeconomic level households, we conducted a descriptive, microbiological, and clinical study. Stools from 59 children with acute community-acquired diarrhea were examined, and their parents were interviewed concerning symptoms and signs. Rotavirus, adenovirus, and norovirus were detected by commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
6

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
(29 reference statements)
0
24
1
6
Order By: Relevance
“…Despite the lack of studies describing in depth the impact of NoV and HAdV in the health of Uruguayan children, all the above-mentioned viruses have been reported as acute gastroenteritis causing agents in Uruguayan paediatric population, with incidences according the expected for RVA (37%) and HAstV (10%). Moreover, a wide dispersion as well as a wide genetic diversity in the Uruguayan environment has been recently reported for these viral pathogens (Victoria et al 2014(Victoria et al , 2016Lizasoain et al 2015;Tort et al 2015;Varela et al 2015;Lopez et al 2017). This information raises the need to evaluate the wastewater treatment process existing in the country to assure viral removal from wastewater and reach effluent of good quality.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the lack of studies describing in depth the impact of NoV and HAdV in the health of Uruguayan children, all the above-mentioned viruses have been reported as acute gastroenteritis causing agents in Uruguayan paediatric population, with incidences according the expected for RVA (37%) and HAstV (10%). Moreover, a wide dispersion as well as a wide genetic diversity in the Uruguayan environment has been recently reported for these viral pathogens (Victoria et al 2014(Victoria et al , 2016Lizasoain et al 2015;Tort et al 2015;Varela et al 2015;Lopez et al 2017). This information raises the need to evaluate the wastewater treatment process existing in the country to assure viral removal from wastewater and reach effluent of good quality.…”
Section: Introductionmentioning
confidence: 97%
“…Dallal identified a frequency of 0.9% for Campylobacter strains in acute diarrhea among children younger than 5 years of age in south Tehran (19). Various studies have reported Campylobacter frequencies, such as 3.0% in Senegal, 8.4% in Uruguay, 9.6% in Egypt, 9.7% in Tanzania, 9.3% in Uganda, 10.5% in Romania, 11.0% in Sudan, 12.7% in Ethiopia, and 22.6% in Ghana (11,12,15,(20)(21)(22)(23)(24)(25). Therefore, the average contribution of Campylobacter strains to AGE in children was about 9% in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, en un estudio que incluyó 59 niños con diarrea aguda, sin tratamiento antibiótico previo, tampoco recuperamos STEC O157 y en cambio se identificaron cepas de los serogrupos O26 y O153. Algo similar ocurrió en otro estudio que incluyó a 249 niños con diarrea aguda sanguinolenta (19,31).…”
Section: Discussionunclassified
“…Para la extracción del ADN bacteriano se utilizó el procedimiento de lisis por calor ya descrito (19).…”
Section: Estudio Microbiológicounclassified
See 1 more Smart Citation